The importance of selected cell adhesion molecules in thyroid cancer - Urbańczuk, Magdalena; Urbańczuk, Marcin; Tuzim, Tomasz; Schab, Katarzyna; Bąk, Kamila; Lewicki, Marcin (Journal of Education, Health and Sport, 2018)
Thyroid cancer is the most common malignant tumour of the endocrine system. It accounts for ca. 2% of all malignant tumours in the world, ranking it 16th in the overall classification. Its most common histology type is the papillary carcinoma originating from the epithelial tissue, which embraces approx. 50-80% of all cases. The epithelial tissue cells in normal conditions are closely interconnected by means of intercellular interactions. The adhesion process is regulated by a series of molecules, called cell adhesion molecules (CAMs). The main representatives of this group, which are increasingly better known and characterised, include the following: E-cadherin, β-catenin, CD44 and CD31 glycoproteins. CAMs regulate the course of many processes, such as differentiation, migration and growth of cells, but they also participate in the transmission of signals to the inside of the cell. Changes in the expression of cell adhesion molecules affect the disruption of the adhesion process. The recent years have seen many scientific reports on the importance of CAMs in the course of neoplastic transformation. It has been proved that abnormalities of CAM expression in many malignant tumours, including the thyroid cancer, are closely related to the increased primary invasion, distant metastasis and worse prognosis. These observations suggest that individual cell adhesion molecules may be used in the future as markers in the diagnostic process of thyroid cancers.